Thermal behaviors in a square duct with U-ribbed tape inserts - Khanoknaiyakarn, Chitakorn; Skullong, Sompol; Promvonge, Pongjet; Jayranaiwachira, Nuthvipa (My University, 2014)
This paper presents an experimental study on thermal characteristics in a constant heatfluxed square-duct heat exchanger with U-ribbed tape inserts. The experiments are carried out by varying airflow rate for Reynolds number ranging from 4000 to 38,000. The insertion of the Uribbed tape is performed with an axial rib-pitch set to four times duct-height (4H) at a single attack angle, α=45° and the ribbed tape is diagonally inserted in the square duct in order to generate longitudinal vortex flows. Effects of five blockage ratios (e/H=0.1, 0.15, 0.2, 0.25 and 0.3) on heat transfer and friction loss are experimentally investigated. The experimental result shows that the insertion of the U-ribbed tape at e/H=0.3 provides the highest heat transfer and friction factor values but the one at e/H=0.25 yields the highest thermal performance enhancement. © (2014) Trans Tech Publications, Switzerland.
Keywords: Friction factor; Heat transfer; Square duct; Thermal behavior; U-shaped ribs